1996
DOI: 10.1063/1.472348
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of the Kr+(2P1/2) state in the reactive quenching of Kr(5s′[1/2]) atoms by halogen-containing molecules

Abstract: Absolute cross sections for photoionization of excited rare gas atoms near threshold: Ar*(4p 3 D 3), Kr*(5p 3 D 3), and Xe*(6s 3 P 0) AIP Conf.The second metastable state of Kr, 5sЈ͓1/2͔ 0 , was generated from the first metastable state, 5s͓3/2͔ 2 , by optical pumping in a flow reactor. Under optimum conditions, the entire Kr͑5s͓3/2͔ 2 ͒ concentration could be removed with more than 40% conversion to the Kr͑5sЈ͓1/2͔ 0 ͒ state, which is stable in He carrier gas. The Kr͑5sЈ͓1/2͔ 0 ͒ and Kr͑5s͓3/2͔ 2 ͒ states hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 62 publications
0
28
0
Order By: Relevance
“…1͑e͒ Some degree of ion-core nonconservation has been seen for Kr* luminescent reactions with halogen-containing molecules. 36 Our preliminary value of about 125 Å 2 for Xe*( 3 P 0 ) is the largest cross section we have measured with our new technique. Also, our experiment for Kr* with the Kr*ϩH 2 O→KrϩOH*ϩH monitor confirms the recent observation by Setser and co-workers 36 that this reaction occurs exclusively for Kr*( 3 P 0 ).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…1͑e͒ Some degree of ion-core nonconservation has been seen for Kr* luminescent reactions with halogen-containing molecules. 36 Our preliminary value of about 125 Å 2 for Xe*( 3 P 0 ) is the largest cross section we have measured with our new technique. Also, our experiment for Kr* with the Kr*ϩH 2 O→KrϩOH*ϩH monitor confirms the recent observation by Setser and co-workers 36 that this reaction occurs exclusively for Kr*( 3 P 0 ).…”
Section: Discussionmentioning
confidence: 67%
“…5. Very recently, Setser and co-workers 36 reported that the Kr*ϩH 2 O→KrϩOH*ϩH reaction originates entirely from Kr*( 3 P 0 ). We undertook one experiment on Kr*ϩO 2 using the aforementioned reaction as a monitor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nonclosed shell of Rg + gives rise to two different excited rare gas halide product states, RgX ‫ء‬ ͑B,⍀ =1/ 2͒ and RgX ‫ء‬ ͑C,⍀ =3/ 2͒, which correlate with Rg + ͑ 2 P 3/2 ͒ and X − ͑ 1 S 0 ͒. The RgX ‫ء‬ formation is known to proceed via the "harpoon" mechanism [22][23][24][25][26][27] such as the metal halide MX formation in the reaction of alkali-metal atoms M, for which steric effects have been widely studied using the oriented molecules. [1][2][3][4][5][6][7][8][9][10][11][12][13][16][17][18] For the KI formation in the K + CF 3 I reaction system, it has been reported that the molecular orientation exerts an influence on only the angular distribution of KI with the comparable reaction probability at the two ends.…”
Section: Introductionmentioning
confidence: 97%
“…The non-closed shell of Rg + gives rise to two different excited rare gas halide product states, RgX* (B, O = 1/2) and RgX* (C, O = 3/2), that correlate with Rg + ( 2 P 3/2 ) and X À ( 1 S 0 ). The RgX* formation is known to proceed via the ''harpoon'' mechanism [24][25][26][27][28][29] like the metal halide MX formations in the reactions of alkali-metal atoms M, for which steric effects have been widely studied using the oriented molecules. [1][2][3][4][5][6][7][8][9][10][11][12][18][19][20][21] For the KI formation in the K + CF 3 I reaction system, it has been reported that the molecular orientation exerts an influence on only the angular distribution of KI with comparable reaction probability at the two ends.…”
Section: Introductionmentioning
confidence: 99%